Testing the Validity of Patellar Measurements in Sex Estimation – A Computed Tomography Study in a Contemporary Polish Population - Karol Jakubik; Mikołaj Jeżak; Aleksandra Nowińska; Monika Grudzień; Piotr Piech; Justyna Karpińska; Grzegorz Staśkiewicz (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Human skeleton-based sex estimation is a major topic of interest for forensic anthropologists. Various bones have been examined for sex heterogeneity. The most commonly used include skull and pelvis, however they may not always be used due to damage or fragmentation. The patella has been shown to be resistant to postmortem changes, which creates a potential use for determining the sex of unknown human remains.